Great Power Conduct and Credibility in World Politics - Smolnikov, Sergey (Springer International Publishing, 2018)
This book seeks to answer one main question: what is the core concern of great powers that streamlines their behavior in the contemporary system of international relations? Building on the examples of the United States, China, Russia, France, and Britain, it tracks both consistency and fluctuations in global power dynamics and great power behavior. The author examines the genesis, causality, and policy implications of decision makers' fixation with retaining a credible image of power in world politics, while exploring how the dynamics of power distribution in international systems modify perceptions of primacy. Drawing on findings from disciplines such as history, economics, social and political psychology, communication theory, philosophy, political science, strategic studies, and above all, from International Relations theory and practice, the volume proposes a novel theory of power credibility, which offers an original explanation of great powers' behavior at the stage of their relative decline. Sergey Smolnikov teaches in the fields of International Relations and Comparative Politics at York University, Canada, and is a former Professor of International Relations at the Graduate Institute for Policy Studies, Tokyo, Japan. .